The standard-setters’ toolkit: can principles prevail over bright lines? - Henderson, Darren; O’Brien, Patricia C. (Review of Accounting Studies, 2017)
We study lease accounting in an international panel data set to examine how accounting outcomes vary with two features of accounting standards: the emphasis on using professional judgement to apply principles, and the presence or absence of bright-line tests. We study four countries—Australia, Canada, the UK, and the US—and companies in two lease-intensive industries—retail and transportation. Our primary study period spans the time when Australia and the UK switched from domestic to international accounting standards, and in one test, we also consider Canada’s transition to international standards. We find that neither an explicit requirement to apply a principle nor omitting bright-line tests materially increases the use of capital lease treatment among these firms. Overall, we conclude that this financial reporting outcome is relatively insensitive to these standard-setting tools.